내용분석(Content Analysis) 및 네트워크 텍스트 분석(Network Text Analysis)을 활용한 국내 서번트 리더십 연구동향 분석 - 최석봉(Suk Bong Choi) (대한경영학회지, 2020)
오늘날과 같이 급변하는 경영환경에서 조직이 지속적으로 성장하고 생존하기 위해서는 리더의 역할이 무엇보다 중요하다. 리더는 구성원들 개개인의 창의성과 역량을 최대로 이끌어 내는 동시에 조직 내 신뢰와 공동체의식을 형성해 내는 것이 필요하다. 이러한 필요성에 따라 새로운 리더십 스타일이 대두되었으며 그 중, 서번트리더십에 대한 관심이 커지고 있다. 본 연구는 국내에서 서번트 리더십 연구가 어떻게 진행되고 있는지 살펴보고 나아가 서번트 리더십 연구의 주요 핵심주제들 간의 관계를 분석하였다. 이를 위하여 서번트 리더십에대한 처음 국내연구가 시작된 2006년이후 2020년까지 한국학술지인용색인에 등록된 KCI 등재지 또는 등재후보지에 게재된 서번트 리더십 논문 70편을 분석하였다. 구체적으로 서번트 리더십의 개념 및 특징을 알아보고내용분석(content analysis) 및 네트워크 텍스트분석(network text analysis)을 시행하였다. 구체적으로 국내연구동향을 연도별, 학술지별, 연구대상별, 연구방법별로 분류하여 국내 연구동향을 체계적으로 분석 하였다. 또한 핵심 연구주제인 주제어를 분석함으로써 어떠한 주제가 활발히 연구되고 있는지 확인하였다. 마지막으로주제어들 간의 네트워크 분석을 통하여 핵심주제 및 이와 연관된 지식구조를 파악하고자 하였다. 분석결과서번트 리더십 연구의 몇 가지 특징을 발견하였다. 먼저, 국내에는 2006년 이후 서번트 리더십 연구가 꾸준히진행되고 있었음을 확인할 수 있었다. 둘째, 학술지별로는 리더십연구, 인적자원관리연구, 대한경영학회지에서서번트 리더십과 관련한 연구가 가장 활발히 이루어지고 있었으며, 이는 특정 학술지에 편중되어 있음을 알수 있었다. 셋째, 연구대상별로 사기업 및 공기업 종사자 대상으로 가장 많은 연구가 이루어졌으며, 공무원, 군인 등과 같은 직군에서는 여전히 연구가 부족함을 확인하였다. 넷째, 연구방법별로 계량적 연구(quantitative research)가 가장 많이 이루어졌으며 질적 연구 및 이론적 연구는 매우 부족하였다. 다섯째, 주제어 빈도분석을통하여 조직시민행동, 조직몰입, 직무만족 등의 변수와 함께 연구가 활발히 이루어지고 있었으며 갈등, 기업성과, 관계지향문화 등과는 연구가 부족한 것을 확인하였다. 마지막으로 네트워크 텍스트 분석을 통하여 조직몰입, 조직시민행동, 성과 등이 가장 중심성이 높게 나타나는 것을 확인하였다. 본 연구의 결과는 서번트 리더십연구의 흐름을 파악하고 서번트 리더십이 어떠한 주제와 연결되어 연구되고 있는지를 구체적으로 제시하였다는데 그 의의가 있다. 또한, 연구 동향을 분석하기 위하여 내용분석 및 네트워크 텍스트 분석을 활용함으로서서번트 리더십 연구의 지식구조를 보다 면밀히 파악할 수 있었다. 이러한 결과는 서번트 리더십 및 리더십을연구하는 향후 연구에 중요한 이론적 실무적 함의가 있다고 할 수 있겠다. The role of leaders is paramount for the growth and survival of organizations in today's rapidly changing business environment. Leaders need to maximize the creativity and competence of each member while forming a sense of trust and community within the organization. In addition, leadership not only affects the achievement of organizational objectives, the establishment of organizational culture, organizational structures and the implementation of strategies, but also induces desirable behavior and attitude changes of organizational members. As a result, leadership has a decisive impact on organizational performance by directly and indirectly affecting the way organizations are operated. Therefore, interest on the servant leadership has been increased by business scholars and managers. In light of this, the present study sought to understand how Korean scholars have carried out the servant leadership research. In addition, this study examined the various relationships between key related variables and servant leadership. More specifically, 70 articles of servant leadership published in Korea citation indexed journals from 2006 to 2020 was collected and reviewed systematically. We firstly discussed the definition and characteristics of servant leadership, and secondly conducted the content analysis and network text analysis to review previous research on servant leadership systematically. In doing so, the previous servant leadership research were classified by year, journal, main topic, and methodology. We then investigated the keywords to identify which research themes were being studied. Lastly, through network text analysis among keywords, we investigated research variables and knowledge structures related to servant leadership studies. The main findings of the analysis are as follows. First of all, it has been confirmed that research on servant leadership has been steadily underway in Korea since 2006. Second, research on servant leadership has shown that it is most actively conducted in the couple of specific journal such as "Journal of Leadership Research", "Human Resource Management Research", and "the Journal of the Korean Management Association". Third, the most studies were conducted on employees of private companies and state-run companies by subject, and it was confirmed that there was still a lack of research in vocational groups such as civil servants and soldiers. Fourth, quantitative research by research method was conducted the most, and qualitative and theoretical research was very insufficient. Fifth, through the contents analysis of the keywords, we could confirm that organizational citizenship behavior, organizational commitment, and job satisfaction were conducted frequently along with servant leadership. However, conflicts, firm performance, and relationship-oriented culture were relatively limited. Sixth, based on through our network text analysis result, we also confirmed that organizational commitment, organizational citizenship behavior, and performance have high centrality. The findings of our study provided the useful research ideas and insight for future research on servant leadership. In addition, our findings have presented important research variables for understanding the effects of servant leadership. Moreover, the knowledge structure of servant leadership research was identified based on content analysis and network text analysis. This study can provide useful implication to the future research and organizational managers who want to enhance servant leadership and its effectiveness in their organization. KCI Citation Count: 0